2014
DOI: 10.1103/physrevlett.113.225701
|View full text |Cite
|
Sign up to set email alerts
|

Role of Structure and Entropy in Determining Differences in Dynamics for Glass Formers with Different Interaction Potentials

Abstract: We present a study of two model liquids with different interaction potentials, exhibiting similar structure but significantly different dynamics at low temperatures. By evaluating the configurational entropy, we show that the differences in the dynamics of these systems can be understood in terms of their thermodynamic differences. Analyzing their structure, we demonstrate that differences in pair correlation functions between the two systems, through their contribution to the entropy, dominate the differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 41 publications
9
88
0
Order By: Relevance
“…Similar to that found earlier 7 , for all the systems, there is initially a positive correlation between the relaxation time and ∆S and as the temperature is lowered the correlation becomes negative. This role reversal of RMPE has been observed earlier where we have reported that the small positive value of RMPE speeds up the relaxation time 37 . Although at moderately high temperatures, the data show a master plot, at low temperature the dependence of relaxation time on RMPE becomes system dependent.…”
Section: Resultssupporting
confidence: 85%
“…Similar to that found earlier 7 , for all the systems, there is initially a positive correlation between the relaxation time and ∆S and as the temperature is lowered the correlation becomes negative. This role reversal of RMPE has been observed earlier where we have reported that the small positive value of RMPE speeds up the relaxation time 37 . Although at moderately high temperatures, the data show a master plot, at low temperature the dependence of relaxation time on RMPE becomes system dependent.…”
Section: Resultssupporting
confidence: 85%
“…At high temperature where RMPE is negative, it slows down the dynamics. The positive value of RMPE actually speeds up the dynamics over the value predicted by the two body part 29 . Thus, its effect on the dynamics is similar to that of activation.…”
Section: Discussionmentioning
confidence: 82%
“…D, η or τ α . It has been tested in many different systems and has proven to be an extremely useful, predictive relationship between dynamics and thermodynamics below the onset temperature [20][21][22][23]26], despite ambiguity about the range of temperatures over which one should expect it to hold ([13]). The breakdown of the SE relation raises the question of which dynamical quantity should obey the Adam-Gibbs relation.…”
mentioning
confidence: 99%
“…Its rationalization is considered fundamental to understanding the glass transition problem [20][21][22][23][24][25][26][27][28][29][30]. The AG relation can be written as X(T ) = X 0 exp A X T Sc(T ) , where X is an appropriate measure of dynamics i.e.…”
mentioning
confidence: 99%